Stridor and parkinsonism. Issue 694 (August 1983) - Read, D.; Young, A.
Abstract : A patient is described with idiopathic Parkinson's disease and severe laryngeal stridor. Other than urinary frequency and urgency, not uncommon in this condition, and postoperative levodopa-sensitive postural hypotension, there were no features of generalized autonomic failure. The laryngeal stridor responded to levodopa therapy, and we are not aware that this has been reported previously.